Effects of strength and speed training for cross-country skiers - Lappalainen, N.; Viertola, V. (2024)
Endurance sports, particularly cross-country skiing, have traditionally focused on endurance. However, recent trends indicate a heightened demand for strength. As authors who previously practiced sports requiring significant strength and speed, we were intrigued by this shift and sought to deepen our understanding of coaching speed and strength in endurance sports.